Polysaccharide export outer membrane proteins in Gram-negative bacteria. (April 2013) - Yuan, Biao; Cheng, Anchun; Wang, Mingshu
Polysaccharide export outer membrane proteins of Gram-negative bacteria are involved in the export of polysaccharides across the outer membrane. The mechanisms of polysaccharide export across the outer membrane in Gram-negative bacteria are not yet completely clear. However, the mechanisms of polysaccharide assembly in Escherichia coli have been intensively investigated. Here, we mainly review the current understanding of the assembly mechanisms of group 1 capsular polysaccharide, group 2 capsular polysaccharide and lipopolysaccharide of E. coli, and the current structures and interactions of some polysaccharide export outer membrane proteins with other proteins involved in polysaccharide export in Gram-negative bacteria. In addition, LptD may be targeted by peptidomimetic antibiotics in Gram-negative bacteria. We also give insights into the directions of future research regarding the mechanisms of polysaccharide export.